2002
DOI: 10.1136/bjo.86.5.536
|View full text |Cite
|
Sign up to set email alerts
|

Acanthamoeba keratitis in England and Wales: incidence, outcome, and risk factors

Abstract: Aim: To determine the incidence, regional variation in frequency, outcome, and risk factors for acanthamoeba keratitis (AK) in England and Wales. Methods: AK cases presenting from 1 October 1997 to 30 September 1999 were identified by the British Ophthalmic Surveillance Unit active reporting system. Clinical and patient postal questionnaire data were analysed. Results: 106 reported cases met study criteria. The annual incidence for the 2 years was 1.26 and 1.13 per million adults and, for contact lens (CL) wea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
243
2
9

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 312 publications
(265 citation statements)
references
References 18 publications
11
243
2
9
Order By: Relevance
“…It has been previously reported that contact lens use is a major risk factor for AK. 1,2,4,8 Although some reports have suggested that the use of daily-disposable lenses poses only a low risk of AK, 5 seven of the AK patients examined in our study used this type of lens. However, it is difficult to use our results to generalise the level of risk of AK as the usage of daily-type contact lenses differs greatly among countries.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…It has been previously reported that contact lens use is a major risk factor for AK. 1,2,4,8 Although some reports have suggested that the use of daily-disposable lenses poses only a low risk of AK, 5 seven of the AK patients examined in our study used this type of lens. However, it is difficult to use our results to generalise the level of risk of AK as the usage of daily-type contact lenses differs greatly among countries.…”
Section: Discussionmentioning
confidence: 91%
“…However, polyhexamethyl biguanide (PHMB) and propamidine isethionate are often used in Western countries. 1,4,[6][7][8] Biguanides such as CHG and PHMB are the most effective cysticidal antiamoebics, and are currently used as a firstline treatment for AK. 9 Lim et al 10 compared the therapeutic outcomes for PHMB and CHG treatment and reported that, although the results were non-significant, 78% of eyes receiving PHMB and 86% of eyes receiving CHG were successfully treated.…”
Section: Introductionmentioning
confidence: 99%
“…There is a lack of recent robust data on the prevalence of Acanthamoeba keratitis in Scotland, but based on a study by Seal et al (1999), the incidence was 149 per million soft contact lens wearers compared with much lower incidence rates of around 18 to 21 per million in the rest of the UK (Radford et al, 2002). Presently, there are approximately 3.7 million contact lens wearers in the UK (British Contact Lens Association, http://www.bcla.org.uk/).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, noncommercial saline solutions have been implicated as potential risk factors (Newton et al, 1986). The UK experienced an increase in cases during the 1990s which coincided with increased use of soft contact lenses (Illingworth et al, 1995).There is a lack of recent robust data on the prevalence of Acanthamoeba keratitis in Scotland, but based on a study by Seal et al (1999), the incidence was 149 per million soft contact lens wearers compared with much lower incidence rates of around 18 to 21 per million in the rest of the UK (Radford et al, 2002). Presently, there are approximately 3.7 million contact lens wearers in the UK (British Contact Lens Association, http://www.bcla.org.uk/).…”
mentioning
confidence: 99%
“…Não há métodos padronizados para se testar a sensibilidade de Acanthamoeba sp às várias medicações, nem métodos para se avaliar a erradicação do parasita, uma vez que a recorrência pode ocorrer. Estudos recentes sugerem que a freqüên-cia da infecção por Acanthamoeba seja igual a 1,2 infectados por ano em cada milhão de adultos no país de Gales e na Inglaterra e de 0,2 a 1 indivíduo para cada 10.000 usuários de lentes de contato por ano (12) . A suspeita diagnóstica precoce determina o melhor prognóstico e depende do reconhecimento de sinais clínicos não específicos.…”
Section: Discussionunclassified